"Every Living Beast Being a Word, Every Kind Being a Sentence": Animals and Religion in Reformation Europe - Parish, Helen L. (Religions, 2019)
The ability of animals to convey meaning, either sacred or profane, features prominently in the dialectic of natural knowledge and sacred histories. Animals, particularly those that exhibited irregularities of nature, symbolised and revealed God's wrath and favour, fulfilling a polemical and pastoral purpose in the communication of God's anger and assiduous care for humanity. The language of readable nature ran through the ancient natural histories of Pliny and Aristotle, the words and images of the medieval bestiaries, and the natural histories and popular discourses of Reformation Europe. In the history of the natural world, 'God's great book in folio', ideas about connections between the written word and human observation, miracles, wonders and providences, were interleaved with theological and biological taxonomies. In so doing, discussions of irregularities and portents in nature expose the conceptualisation of human relationships with the world, with the past, with the present, and with the divine. This article explores the connections between real and symbolic animals, religious, and the plasticity of God's creation in the natural histories and polemical literature of the Reformation. It explores the multivalent positioning of particular sea creatures as providential signs of God's continued presence in the world, natural phenomena, and man-made objects, and the ongoing syncretism between natural history, religion, ancient texts and human observation in the dialectic of this period.